2004
DOI: 10.1590/s1678-58782004000100005
|View full text |Cite
|
Sign up to set email alerts
|

GMAW welding optimization using genetic algorithms

Abstract: This article explores the possibility of using Genetic Algorithms (GAs) as a method to decide near-optimal settings of a GMAW welding process. The problem was to choose the near-best values of three control variables (welding voltage, wire feed rate and welding speed) based on four quality responses (deposition efficiency, bead width, depth of penetration and reinforcement), inside a previous delimited experimental region. The search for the near-optimal was carried out step by step, with the GA predicting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…The study by Sathiya et al 7 exposed an overall idea of the optimization of friction welding parameters using different techniques. Correia et al 8 proposed a method to decide near-optimal settings of a GMAW welding process. Near-best values of three control variables (welding voltage, wire feed rate and welding speed) based on four quality responses (deposition efficiency, bead width, depth of penetration and reinforcement), inside a previous delimited experimental region were chosen.…”
Section: Weldability Studies and Parameter Optimization Of Aisi 904lmentioning
confidence: 99%
“…The study by Sathiya et al 7 exposed an overall idea of the optimization of friction welding parameters using different techniques. Correia et al 8 proposed a method to decide near-optimal settings of a GMAW welding process. Near-best values of three control variables (welding voltage, wire feed rate and welding speed) based on four quality responses (deposition efficiency, bead width, depth of penetration and reinforcement), inside a previous delimited experimental region were chosen.…”
Section: Weldability Studies and Parameter Optimization Of Aisi 904lmentioning
confidence: 99%
“…To overcome this problem, the response surface methodology uses the near-optimal values as a reference point to obtain a model of the welding process and determine optimal values of the process variables. Correia et al (2004) adopted a similar approach, where a GA was used as a tool to decide near-optimal settings of a GMAW process. The search for the near-optimal settings was carried out step by step with the help of a GA predicting the next experiment based on the previous, and without using the knowledge of the modeling equations between the inputs and outputs of the GMAW process.…”
Section: Literature Surveymentioning
confidence: 99%
“…Correia et al [6] investigated the implementation possibility of using GA as a method to decide near optimal settings of a GMAW process and compared its performance with RSM. Kim et al [21] suggested a GA and RSM combined approach for determining optimal welding conditions.…”
Section: Introductionmentioning
confidence: 99%